Doing the Right Thing or Doing the Thing Right: Allocating Resources Between Marketing Research and Manufacturing - Hess, James D.; Lucas, Marilyn T. (Management Science, 2004)
Matching production with sales potential is essential for survival in volatile markets. Manufacturing and marketing managers compete for staff, space, cash, and other assets as they struggle both to determine what and how many products ought to be produced, and to actually produce them. We develop an analytical framework to answer one simple question, “How much marketing research should a firm do when it takes resources away from manufacturing the goods that generate revenue?” To understand the costs and benefits of marketing research, we account for the lost opportunities to produce these goods. Some analytical findings are striking: firms without initial knowledge of their potential customers should allocate one-third of the firm's resources to marketing research. The model suggests a host of issues to be more deeply studied by management scientists.